The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting–Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz–and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Section: 373 pages
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Macmillan, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques